Effects of emotional intelligence on knowledge sharing among employees: A study of HoReCa companies in Turkey - Sabahattin Çetin (Ural State University of Economics, 2021)
Information and knowledge play a significant role in helping organizations to gain competitive advantages by delivering unique products or services. The dissemination of knowledge within an organization depends on the knowledge sharing behaviour exhibited by the members of this organization. The study aims to examine the effects of emotional intelligence on knowledge sharing behaviour. The methodological basis of the research includes the theoretical concepts of knowledge sharing and emotional intelligence. Within the scope of the study, data were collected through convenience sampling method from 454 employees working in hotels in Bartin, Ankara and Antalya provinces. To interpret the data, descriptive statistics, as well as correlation and regression analysis were performed using SPSS software. The research results demonstrate that among the dimensions of emotional intelligence, understanding emotion, emotion management and social management skills positively affect knowledge sharing behaviour, whereas perceiving emotion and using emotion skills are found to have no significant effect on this behaviour. The authors arrive at the conclusion that individuals with high emotional intelligence tend to exhibit more knowledge sharing behaviour and are more prone to disseminate information in the organization.